2020
DOI: 10.3390/jcm9040999
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Probiotics on Symptoms, Gut Microbiota and Inflammatory Markers in Infantile Colic: A Systematic Review, Meta-Analysis and Meta-Regression of Randomized Controlled Trials

Abstract: Immaturity in digestive-tract motor function and altered intestinal microbiome may play roles in pathogenesis of infantile colic. We assessed the impact of probiotic therapy on crying duration day, in newborns experiencing colic attacks. The PubMed, Embase, Cinnahl, Web of Science databases, and a clinical trials registry (ClinicalTrials.gov) were searched from inception until 12/02/2020. Random-effects meta-analyses were used to derive standardized mean differences/differences in means and risk ratios. We inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 83 publications
(205 reference statements)
0
17
0
5
Order By: Relevance
“…The potential of calmodulin as a growth modulator has already been demonstrated in other systems (Nelson et al, 1997;Takuwa et al, 1995a,b) and work is underway to understand the direct impact of calmodulin and calcium in black soldier fly development and waste conversion. Being black soldier fly larvae are known to be high in calcium (Johannsen, 1922), the potential link with our discovery is that bacterial supplementation enhanced calcium deposition in the exoskeleton Probiotics are live microorganisms that, when administered in adequate amounts, confer a health benefit on the host (Skonieczna-Zydecka et al, 2020). All members of the Animalia kingdom, including humans, have helpful symbiotic microbiota which are extremely important for the proper functioning of the gastrointestinal tract, and now products are being commonly used as dietary supplements.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The potential of calmodulin as a growth modulator has already been demonstrated in other systems (Nelson et al, 1997;Takuwa et al, 1995a,b) and work is underway to understand the direct impact of calmodulin and calcium in black soldier fly development and waste conversion. Being black soldier fly larvae are known to be high in calcium (Johannsen, 1922), the potential link with our discovery is that bacterial supplementation enhanced calcium deposition in the exoskeleton Probiotics are live microorganisms that, when administered in adequate amounts, confer a health benefit on the host (Skonieczna-Zydecka et al, 2020). All members of the Animalia kingdom, including humans, have helpful symbiotic microbiota which are extremely important for the proper functioning of the gastrointestinal tract, and now products are being commonly used as dietary supplements.…”
Section: Discussionmentioning
confidence: 87%
“…Probiotics are recommended to be added not only to the human diet but also into the forage of different vertebrates as well as invertebrates (Ptaszynska et al, 2016;Skonieczna-Zydecka et al, 2020;Uyeno et al, 2015;Wang et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Results of a recent systematic review and meta-analysis of clinical trials have demonstrated that probiotics could reduce the crying episodes in infants with IC. They concluded that based on available data we could not concisely assume that probiotics could improve IC by modulation of immune system or modulation of microbiota because most of the reviewed studies reported their data based on associations and recommended to plan further clinical trials base on causations [19].…”
Section: Discussionmentioning
confidence: 99%
“…Another study indicated that BB-12 has a bene cial action on transit time and stool consistency [14]. Probiotics(I.e: BB-12) may intermingle with the immune system in several ways, e.g., by provoking local and systemic antibody production, by aggravating immune cell activity, by modifying signals in epithelial and immune cells, and by stimulation of phenotypic alterations in dendritic cells [23].However, the main mechanism of this effect is still unclear; and a causal relationship between the modulatory effect of probiotics on microbiota and the immune system has not been absolutely con rmed [19].…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of randomized controlled trials in term infants with colic demonstrated a significant decrease in crying time with probiotic administration. The probability of a >50% reduction in crying time was close to 2-fold higher [ 132 ]. The European Society for Paediatric Gastroenterology and Hepatology recently released a conditional recommendation for probiotic use in preterm infants for the prevention of NEC [ 133 ] based on a strain-specific network analysis of clinical trials [ 134 ].…”
Section: Attempts To Attenuate Neonatal Intestinal Dysbiosismentioning
confidence: 99%